CSR and employee empowerment: scale development and validation / Noor Adwa Sulaiman and Rusnah Muhamad - Sulaiman, Noor Adwa; Muhamad, Rusnah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This study develops a measurement scale to assess the contribution of companies' corporate social responsibility (CSR) programmes on employees' empowerment. Data from a self-administered questionnaire completed by 45 respondents were tested using exploratory factor analysis and reliability for scale validation. The results show two constructs, namely authority and ability, consisting of ten items, were found to be reliable and valid in assessing the CSR-Empowerment attributes. The developed scale could be used by companies as an instrument to assess CSR programmes, thereby assisting interested parties (regulators, researchers and companies) in evaluating the impact of the CSR programmes in empowering employees.